Functionalized layered double hydroxides composite bio-adsorbent for efficient copper(II) ion encapsulation from wastewater - Khandaker, S.; Hossain, M.T.; Saha, P.K.; Rayhan, U.; Islam, A.; Choudhury, T.R.; Awual, Rabiul (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
In this study, naturally abundant and inexpensive bamboo was used to make cheaper activated charcoal for efficient encapsulation of toxic copper (Cu(II)) ion from wastewater. The functionalized bamboo charcoal-Layered double hydroxides (BC-LDHs) composite bio-adsorbent was prepared using co-precipitation method. The composite bio-adsorbent was exploited to eliminate Cu(II) ion with high sensitivity and selectivity from contaminated water. The adsorption parameters including the effect of pH, contact time, adsorbent dose, and effect of initial concentration were optimized in systematic way and the adsorption kinetics and isotherms were investigated for potential use in real sample treatment. The physicochemical properties and morphological structure of the adsorbent were examined using X-ray Diffraction, Scanning Electronic Microscopy, Fourier Transform Infrared Spectroscopy and Thermogravimetric Analysis to understand the Cu(II) ion adsorption mechanism. The adsorption results revealed that the BC-LDH could remove almost 100% of Cu(II) ion from aqueous solution at pH range between 3.0 and 6.0 within 30 min. The maximum monolayer adsorption capacity was determined to be 85.47 mg/g based on the Langmuir isotherm. The adsorption equilibrium data were well-fitted by the Langmuir isotherm model (R2 = 0.998) and the experimental kinetic data were supported by the pseudo-second order model (R2 = 0.999). The BC-LDH could be reused without losing its adsorption performance in several cycles after successful regeneration with 0.10 M HCl. The Cu(II) ion removal mechanism was postulated with intercalated ion exchange, surface precipitation and interaction between BC-LDH and surface functionalities. Therefore, the highly functional BC-LDH composite could be a promising adsorbent for efficient Cu(II) ion removal from wastewater.